Atender y responder - Mena Malet, Patricio (ARFIL y UNL, 2018)
This paper tries to interrogate the verb “to attend” in its double acceptation, as perceptive attention and as care. What seems interesting in the study of the link between both meanings is that it puts into play a subject who understands himself or herself in strict relationship with an otherness whose way of being is determined by his or her answers. In this sense, the progressive examination that goes from perceptive attention to attention as care brings important resources to think the responsive dimension of the self under the auspices of contemporary phenomenology: Ricoeur, but also Levinas, Marion, Chrétien, Housset and Romano.